Implementation of Strategic Management in Optimizing Merdeka Curriculum - Nuryani, Nuryani; Ahyani, Nur; Mahasir, Mahasir (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to describe and analyze the implementation of strategic management in optimizing Merdeka Curriculum at SMA Negeri 3 Unggulan Kayuagung. This study uses qualitative methods. It shows that Implementation of strategic management consists of strategy formulation (environmental analysis, vision, mission, goals, targets and strategies), implementation (operational curriculum, programs, monitoring and communication systems, school resources, organizational structure, school’s principal leadership, and work culture), and strategy evaluation. The obstacles are dynamic policies, limited time, work completion gaps, inconsistency, and evaluation document. The solutions are to optimize growth mindset, digitalization; priority scale-based work plans; collaboration culture; performance work management; evaluation instruments and action plans. Novelty of this study resides in the research setting that implements the Merdeka Curriculum with Mandiri Berbagi category, so this study can contribute to strengthening strategic management in educational units to achieve optimal results in facing changes in the Merdeka Curriculum category options.